2002
DOI: 10.1006/jmsc.2002.1306
|View full text |Cite
|
Sign up to set email alerts
|

The use of adaptive cluster sampling for hydroacoustic surveys

Abstract: Resource managers are often required to estimate the size of a wildlife population based on sampling surveys. This problem is especially critical in fisheries, where stock-size estimation forms the basis for key policy decisions. This study looks at design-based methods for a hydroacoustic fisheries survey, with the goal of improving estimation when the target stock has a patchy spatial distribution. In particular, we examine the efficiency and feasibility of a relatively new design-based method known as adapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 40 publications
0
25
0
1
Order By: Relevance
“…Conners and Schwager (2002) have shown that a simple sample mean may have a strong nonnormal distribution when transects are sampled from a spatially clustered population. If the distribution of paddlefish or other large fishes is clustered, then results such as these may violate the standard design assumption that target organisms are evenly distributed in space such that each transect may be considered a random draw from an identical underlying distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Conners and Schwager (2002) have shown that a simple sample mean may have a strong nonnormal distribution when transects are sampled from a spatially clustered population. If the distribution of paddlefish or other large fishes is clustered, then results such as these may violate the standard design assumption that target organisms are evenly distributed in space such that each transect may be considered a random draw from an identical underlying distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Cluster sampling techniques are appropriate for acoustic data, which represent a continuous stream of autocorrelated data (Williamson 1982;Connors and Schwager 2002). Density and biomass values for each ESDU in each stratum were weighted by dividing the stratum area (measured using GIS) by the number of ESDUs in the stratum.…”
Section: Estimates Of Fish Abundance and Biomassmentioning
confidence: 99%
“…Some recent examples are the use of adaptive cluster sampling for surveys of plants [25], waterfowl [31], seaweed [13]), shellfish [33], marsupials [30], forests [35,18], herpetofauna [23], larval sea lampreys [34]), sediment load in rivers [2]), in hydroacoustic surveys [10] and fish eggs [16].…”
Section: Fig 1 Adaptive Cluster Sampling Of Blue-winged Teal (From mentioning
confidence: 99%